Digital CRISPR/Cas‐Assisted Assay for Rapid and Sensitive Detection of SARS‐CoV‐2. Issue 5 (12th January 2021) - Park, Joon Soo; Hsieh, Kuangwen; Chen, Liben; Kaushik, Aniruddha; Trick, Alexander Y.; Wang, Tza‐Huei
Abstract: The unprecedented demand for rapid diagnostics in response to the COVID‐19 pandemic has brought the spotlight onto clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated systems (Cas)‐assisted nucleic acid detection assays. Already benefitting from an elegant detection mechanism, fast assay time, and low reaction temperature, these assays can be further advanced via integration with powerful, digital‐based detection. Thus motivated, the first digital CRISPR/Cas‐assisted assay—coined d igitization‐e nhanced C RISPR/Cas‐assisted o ne‐pot vi rus d etection (deCOViD)—is developed and applied toward SARS‐CoV‐2 detection. deCOViD is realized through tuning and discretizing a one‐step, fluorescence‐based, CRISPR/Cas12a‐assisted reverse transcription recombinase polymerase amplification assay into sub‐nanoliter reaction wells within commercially available microfluidic digital chips. The uniformly elevated digital concentrations enable deCOViD to achieve qualitative detection in <15 min and quantitative detection in 30 min with high signal‐to‐background ratio, broad dynamic range, and high sensitivity—down to 1 genome equivalent (GE) µL −1 of SARS‐CoV‐2 RNA and 20 GE µL −1 of heat‐inactivated SARS‐CoV‐2, which outstrips its benchtop‐based counterpart and represents one of the fastest and most sensitive CRISPR/Cas‐assisted SARS‐CoV‐2 detection to date. Moreover, deCOViD can detect RNA extracts from clinical samples. Taken together, deCOViD opens a new avenue for advancing CRISPR/Cas‐assisted assays and combating the COVID‐19 pandemic and beyond. Abstract : A digital clustered regularly interspaced short palindromic repeats (CRISPR)/Cas‐assisted nucleic acid detection assay is created by discretizing a one‐step, fluorescence‐based, CRISPR/Cas12a‐assisted reverse transcription recombinase polymerase amplification assay within sub‐nanoliter reaction wells of a commercial microfluidic digital chip, which enables quantitative detection of 1 genome equivalent µL −1 of SARS‐CoV‐2 RNA in <30 min—one of the fastest and most sensitive CRISPR/Cas‐assisted detection to date.